(untitled) (KMC Journal, 2025)
Developing freewriting skills presents significant challenges for Nepalese English language learners. Students in Nepali medium schools often face various difficulties in acquiring freewriting skills which hinder their overall English language learning. This action research identifies the challenges encountered by Grade 10 students at Sudurpashchim Secondary School in developing freewriting skills and proposes effective strategies to address these issues. To achieve this, a qualitative action research approach was employed, involving classroom observations, students’ writing samples, and focus group discussion with students. Data were collected over a six-week intervention period during which the researcher implemented a series of freewriting activities tailored to the students’ needs. The analysis focused on identifying recurring difficulties, student perceptions, and observable changes in writing fluency and confidence. The findings reveal that the students struggle due to poor English language backgrounds, inadequate grammar knowledge, limited writing exposure, anxiety, and a lack of awareness of freewriting strategies. These factors lead to difficulties in constructing even grammatically correct sentences, writing cohesive paragraphs, and composing basic descriptive essays. The research highlights that employing translanguaging and personalization approaches significantly enhanced the students’ freewriting abilities. These techniques proved effective for learners with limited English proficiency and difficulties in generating ideas. The study emphasizes the importance by analyzing classroom challenges before designing action plans to address students’ specific needs effectively. The results suggest that teachers should integrate these strategies into their instruction to improve students’ freewriting skills. Such approaches not only address linguistic gaps but also enhance confidence and creativity in students, contributing to their overall language development.